Penentuan Sektor Unggulan di Kabupaten Kepulauan Anambas - Ruth Yuliani Hutabarat (Universitas Samudra, 2020)
This paper aims to analyze the leading sectors of the economy in Kepulauan Anambas Regency. The data analysis method used is the Location Quotient (LQ), Shift-Share, and Klassen Typology, with the analysis area of Kepulauan Anambas Regency and the reference area of Kepulauan Riau Province. Based on LQ analysis, it is known that the leading sector of Kepulauan Anambas Regency is Agriculture, Forestry, and Fisheries sector, as well as Mining and Quarrying sector. Based on Shift-Share analysis, it is known that the Construction sector and Health Services and Social Activities sector are sectors with rapid growth, while the Agriculture, Forestry, and Fisheries sectors are stunted but growing sectors. Based on the Klassen Typology analysis, it is found that the Agriculture, Forestry and Fisheries Sector is the leading sector and has rapid growth. While the Mining and Quarrying sector is the leading sector but the growth is stunted. The Construction sector, Real Estate sector, and Health Services and Social Activities sector which are potential sectors and can still be developed.